Kenya : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
Kenya showed low economic performance owing to governance problems and the slow pace of structural reforms. Executive Directors emphasized the need to lower public debt and tighten fiscal and monetary policies. They commended the anticorruption strategy and advised to improve governance, reform the tax system, and ensure fiscal sustainability. They stressed the need to align the Poverty Reduction Strategy Program (PRSP) to the budget and to strengthen public expenditure policy and banking supervision. They welcomed the decision of implementing the full PRSP and emphasized the need to implement the program without interruption.